Without precedent: Shifting protocols in the use of Rongelapese navigational knowledge - Genz, Joseph H. (Waka Kuaka, 2017)
The cultural revitalisation of voyaging in the Marshall Islands is gaining momentum under extraordinary social conditions involving shifting protocols in the use of navigational knowledge. The first phase of the project (2005-2009) facilitated an elder from Rongelap in achieving the social status of a titled navigator, a process that involved delicate negotiation between chiefly permission to share knowledge and the resulting loss of meaning and prestige. For the first time, the sharing of the Rongelapese knowledge extended beyond direct family lines of inheritance to an apprentice navigator. The second phase of the project (2010-2015) involved the apprentice undertaking a voyage without the guidance of the master navigator. I contend that an apprentice navigator demonstrating his prowess without the teacher is unprecedented under the enduring chiefly protocols on the restricted use of specialist knowledge in the Rongelapese community, but that such a shift in etiquette might be the only viable path to ensure cultural survival amidst encroaching environmental and social impacts.